High-dose dexamethasone regulates microglial polarization via the GR/JAK1/STAT3 signaling pathway after traumatic brain injury - Mengshi Yang; Miao Bai; Yuan Zhuang; Shenghua Lu; Qianqian Ge; Hao Li; Yu Deng; Hongbin Wu; Xiaojian Xu; Fei Niu; Xinlong Dong; Bin Zhang; et al. (Neural Regeneration Research, 2025)
Although microglial polarization and neuroinflammation are crucial cellular responses after traumatic brain injury, the fundamental regulatory and functional mechanisms remain insufficiently understood. As potent anti-inflammatory agents, the use of glucocorticoids in traumatic brain injury is still controversial, and their regulatory effects on microglial polarization are not yet known. In the present study, we sought to determine whether exacerbation of traumatic brain injury caused by high-dose dexamethasone is related to its regulatory effects on microglial polarization and its mechanisms of action. In vitro cultured BV2 cells and primary microglia and a controlled cortical impact mouse model were used to investigate the effects of dexamethasone on microglial polarization. Lipopolysaccharide, dexamethasone, RU486 (a glucocorticoid receptor antagonist), and ruxolitinib (a Janus kinase 1 antagonist) were administered. RNA-sequencing data obtained from a C57BL/6 mouse model of traumatic brain injury were used to identify potential targets of dexamethasone. The Morris water maze, quantitative reverse transcription-polymerase chain reaction, western blotting, immunofluorescence and confocal microscopy analysis, and TUNEL, Nissl, and Golgi staining were performed to investigate our hypothesis. High-throughput sequencing results showed that arginase 1, a marker of M2 microglia, was significantly downregulated in the dexamethasone group compared with the traumatic brain injury group at 3 days post–traumatic brain injury. Thus dexamethasone inhibited M1 and M2 microglia, with a more pronounced inhibitory effect on M2 microglia in vitro and in vivo. Glucocorticoid receptor plays an indispensable role in microglial polarization after dexamethasone treatment following traumatic brain injury. Additionally, glucocorticoid receptor activation increased the number of apoptotic cells and neuronal death, and also decreased the density of dendritic spines. A possible downstream receptor signaling mechanism is the GR/JAK1/STAT3 pathway. Overactivation of glucocorticoid receptor by high-dose dexamethasone reduced the expression of M2 microglia, which plays an anti-inflammatory role. In contrast, inhibiting the activation of glucocorticoid receptor reduced the number of apoptotic glia and neurons and decreased the loss of dendritic spines after traumatic brain injury. Dexamethasone may exert its neurotoxic effects by inhibiting M2 microglia through the GR/JAK1/STAT3 signaling pathway.